HAK DAN KEWAJIBAN BENDAHARAWAN INSTANSI PEMERINTAH DALAM PEMUNGUTAN PAJAK PENGHASILAN DI KABUPATEN PIDIE - Yusmadi, Dahlan, Mahdi Syahbandir. (Jurnal Ilmu Hukum, 2014)
Abstract: The implementation of the obligation of the person paying the tax at the governmental institution in collecting income tax in Pidie District has not been conducted well, it can be seen from the fact that there are the people in Regional Official Working Unit that are late in transferring it to the Tax Service Office as they are not fulfilling their duties relating the taxation based on existing rule causing the income of the state from the tax is having a trouble and it is prone to making loss to the state. The cause factors that the people do not transferring the collected income tax that has been collected are lack of understanding regarding the obligation of taxation, lack of coordination with the taxation officials, lack of campaign regarding how to pay the tax, to collect tax and to cut it and how to report it by the Governmental Obliged Tax Payer. The juridical consequence on the officers that is not fulfilling the collection and transferring it to the state are he will be sentenced criminally based on the criminal rule on the Act of Taxation especially regarding the rule on Income Tax of the Act. Keywords: The contents of the MoU and the Act of Aceh Governance Abstrak: Pelaksanaan kewajiban bendaharawan instansi pemerintah dalam pemungutan pajak penghasilan di Kabupaten Pidie belum berjalan sebagaimana mestinya hal ini ditunjukkan dengan adanya bendahara pada Satuan Kerja Perangkat Daerah (SKPD) yang terlambat dalam penyetoran pajak penghasilan ke Kantor Pelayanan Pajak karena bendahawaran yang tidak sepenuhnya melaksanakan kewajiban perpajakan sesuai dengan ketentuan yang berlaku yang berakibat pada penerimaan negara dari sektor pajak juga mengalami kendala dan berpotensi merugikan negara. Faktor penyebab bendaharawan instansi pemerintah tidak menyetorkan pajak penghasilan yang telah dipungut antara lain, rendahnya pemahaman terhadap kewajiban perpajakan, lemahnya koordinasi dengan petugas perpajakan (fiskus), kurangnya penyuluhan tentang tata cara pembayaran pajak, pemotongan pajak dan pemungutan pajak serta tata cara pelaporan pajak oleh wajib pajak instansi pemerintah. Konsekwensi yuridis bagi bendaharawan instansi pemerintah yang tidak melaksanakan pemungutan dan penyetoran pajak penghasilan adalah bendahara yang bersangkutan dapat dikenakan sanksi sebagaimana yang diatur dalam ketentuan pidana UU Perpajakan khususnya UU PPh. Kata kunci: Bendaharawan dan Pajak Penghasilan